French business dictionary : the business terms of France and Canada - Bousteau, Agnes; Boisvert, Simon (Schreiber Publishing, 2005)
This is the next generation of business dictionaries. Including modern banking, accounting, insurance, real estate, import-export, taxes, business law and computer terms, this is an essential resource for those working in multilingual, multicultural business fields.